2016
DOI: 10.1038/srep29751
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atopic Dermatitis in Chinese Children aged 1–7 ys

Abstract: Prevalence of atopic dermatitis (AD) is increasing worldwide. Up to date, there has been no face-to-face nation-wide study in China. We aim to explore the prevalence of clinical diagnosed AD in children aged 1–7 ys in China. Twelve metropolises were chosen from different areas of China. In each region, we selected 4–10 kindergartens and 2–5 vaccination clinics randomly. A complete history-taking and skin examination were performed by dermatologists. The definite diagnosis of AD and the severity were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 36 publications
9
98
5
2
Order By: Relevance
“…Atopic dermatitis prevalence is 30.48% in Chinese infants aged 1–12 months, which is much higher than that in the children aged 1–7 years (12.94%) . A higher prevalence of AD in infants is consistent with our previous findings that the disease prevalence decreases with age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Atopic dermatitis prevalence is 30.48% in Chinese infants aged 1–12 months, which is much higher than that in the children aged 1–7 years (12.94%) . A higher prevalence of AD in infants is consistent with our previous findings that the disease prevalence decreases with age.…”
Section: Discussionsupporting
confidence: 90%
“…Two birth cohort studies in Germany have suggested that AD greatly improves or resolves until late childhood in up to 70% of cases, and that early and severe onset, family history of AD, and early allergen sensitizations are risk factors for a persistent course . Our previous study in children aged 1–7 years in China showed that the proportion of mild, moderate and severe AD was 74.60%, 23.96% and 1.44%, respectively. Thus, the combination of data from the infant group with those from the 1‐ to 7‐year‐old group in China indicates that not only severity but prevalence of AD often decreases with age.…”
Section: Discussionmentioning
confidence: 90%
“…[2] It used to be that AD was an infantile disease, but in this investigation, the proportion of adults in AD is greater than children. Both the overall incidence of AD and the proportion of adults in AD are clearly on the rise in China, which attested late-onset AD is a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In China, the overall prevalence of AD in 2016 is reported to be 12.94% by clinical diagnosis of dermatologists, while based on UK diagnostic criteria, it is 4.76% in children aged 1 to 7 years. [2] Very few studies have focused on adult AD, despite the fact that the occurrence of adult AD has obviously influenced socioeconomic conditions in both Asian and Western countries. [3,4] According to a study in Taiwan from August 2007 to May 2008, 90 adult patients with AD (8%) were identified by dermatologists’ diagnosis among nursing staff in a Taiwanese medical center.…”
Section: Introductionmentioning
confidence: 99%
“…A descriptive cross‐sectional study conducted in eight different districts in Shanghai in 2010 that included 10 436 children found a prevalence of AD of 8.3% . In addition, results of an epidemiological study conducted in 2013 and 2014 in 12 metropolises throughout China and including 13 998 children 1–7 years of age showed a prevalence of 12.94% (ranging 9.00–24.69% between metropolises) . Similar to other countries, there has been a trend of increasing prevalence of AD in China, with one study that compared ISAAC phase 1 data and ISAAC phase 3 data in children in Guangzhou City showing that the prevalence of AD in children aged 13–14 years increased from 1.7% in 1994–1995 to 3.0% in 2001 …”
Section: Ad Epidemiology In Asiamentioning
confidence: 96%